Swift 5 programming for beginners - Walter, Nick (Packt Publishing, 2019)
"Learn to Code Swift 5 with Mac's Xcode Playgrounds or Linux or Windows. make iOS 12 iPhone Apps or Command Line Tools. Swift is a programming language that allows you to write software for iPhones, iPads, Macs, Apple Watches, Apple TVs, desktops, servers, and anything else that runs code! Swift is great for new programmers because it is very intuitive and continues to evolve as Apple adds new features. It is relatively easy to catch software bugs in Swift and you can check the results immediately by running code in a playground. Also, Swift is open source, so you can take this course even if you are using a Linux or Windows computer! Come learn what's new in Swift 5 and gain a new skill!"--Resource description page